Decisões e desafios em um processo de formação de pós-graduação para gestão educacional - Sosa Sálico, Milagros (Universidad Nacional del Litoral, 2019)
In this article, we describe and analyze partof a postgraduate training process carried out withinthe framework of an agreement between UniversidadNacional del Litoral (UNL) and the provincial Ministryof Education (MEP, for its Spanish initials): the Master’sDegree in Public Policies for Education (MPPE).The objective of this Master's Degree was to provideconceptual and methodological frameworks linked tothe management and governance of institutions at differentscales and levels within the education system,particularly focusing on the province of Santa Fe. Weorganized the analysis of the experience into four sections:the first one takes up the general framework of theemergence of the master's degree project; the secondsection describes design and implementation features of the second cohort, especially aimed at managersin the provincial education system; and the third onedescribes the development of two instances of this trainingprocess: a Final Work-Support Workshop andInternships. Both were relevant to academic productionand in light of the discussion on management practices.Finally, reflections are shared around the implications ofthis experience, which are considered as contributionsto both the improvement of a process of managerialtraining and the optimization of public policies sharedby university and MEP.